Governance in a globalizing world - Nye, Joseph S.; Donahue, John D. (Visions of Governance for the 21st Century ; Brookings Institution Press, 2000)
Far from being another short-lived buzzword, "globalization" refers to real changes. These changes have profound impacts on culture, economics, security, the environment -- and hence on the fundamental challenges of governance. This book asks three fundamental questions: How are patterns of globalization currently evolving? How do these patterns affect governance? And how might globalism itself be governed? The first section maps the trajectory of globalization in several dimensions -- economic, cultural, environmental, and political. For example, Graham Allison speculates about the impact on national and international security, and William C. Clark develops and evaluates the concepts of "environmental globalization." The second section examines the impact of globalization on governance within individual nations (including China, struggling countries in the developing world, and the industrialized democracies) and includes Elaine Kamarck's assessment of global trends in public-sector reform. The third section discusses efforts to improvise new approaches to governance, including the role of non-governmental institutions, the global dimensions of information policy, and Dani Rodrik's speculation on global economic governance